Integrasi Islam dan Negara dalam Pemikiran Politik Gus Dur - Salamah Eka Susanti (HUMANISTIKA : Jurnal Keislaman, 2017)
Gus Dur is a well-known figure in the movement as a figure who fight for democracy, pluralism, inclusive Islam, justice, compassion and human rights. For Abdurrahman, Islam is a religion of love and tolerance all at once a religion of justice and honesty. This means that Islam is egalitarian beliefs, beliefs that fundamentally does not support the discriminatory treatment. Gus Dur appreciation of Islam as a religion that is very inclusive and egalitarian coloring every thought, attitude and consistency in every discourse that he developed. Gus Dur human dignity looked the same, although there are differences between them. Gus Dur is believed that the man honored as God’s creation. Therefore, he thinks Islam is a faith that recognizes that in the eyes of God, all human beings are equal. Even the status of Muslims and non-Muslims are the same. If God only human respect, why people do not respect fellow human beings? Human dignity comes from God the Creator. Social differences in race, gender and gender should not be a reason for the difference in dignity or differences in rights and duties as citizens.